2004
DOI: 10.1123/tsp.18.3.252
|View full text |Cite
|
Sign up to set email alerts
|

An Imagery Intervention during the Competitive Season with an Elite Rugby Union Player

Abstract: The purpose of the present study was to explore the use of imagery by an elite rugby union football player and to examine the effects of an imagery intervention in a practical performance environment. The study took place over a 14-week period of the competitive season. Data collection comprised semi-structured interviews, diaries, and the Sport Imagery Questionnaire. The findings suggested that the participant primarily used cognitive specific and cognitive general imagery. Post-intervention, the participant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 24 publications
1
40
0
5
Order By: Relevance
“…Furthermore, even when all eight skills have been measured in research (e.g., Frey, Laguna, & Ravizza, 2003), the authors have not always reported subscale scores and instead have collapsed all the psychological skills from the TOPS into a single psychological-skill score (thus negating the variety of skills within the TOPS). The four skills have also received widespread attention in both single-skill (e.g., Evans, Jones, & Mullen, 2004;Johnson, Hrycaiko, Johnson, & Halas, 2004) and multiple-skill (e.g., Hanton & Jones, 1999;Thelwell, Greenlees, & Weston, 2006) applied studies. Finally, although we acknowledge the alternative psychological skills used in sporting performance, they decided to limit the number of skills to the four mentioned previously, given that this article represents the first study examining psychological skills in a coaching context.…”
mentioning
confidence: 99%
“…Furthermore, even when all eight skills have been measured in research (e.g., Frey, Laguna, & Ravizza, 2003), the authors have not always reported subscale scores and instead have collapsed all the psychological skills from the TOPS into a single psychological-skill score (thus negating the variety of skills within the TOPS). The four skills have also received widespread attention in both single-skill (e.g., Evans, Jones, & Mullen, 2004;Johnson, Hrycaiko, Johnson, & Halas, 2004) and multiple-skill (e.g., Hanton & Jones, 1999;Thelwell, Greenlees, & Weston, 2006) applied studies. Finally, although we acknowledge the alternative psychological skills used in sporting performance, they decided to limit the number of skills to the four mentioned previously, given that this article represents the first study examining psychological skills in a coaching context.…”
mentioning
confidence: 99%
“…Os resultados deste estudo ao comprovarem a possibilidade dos atletas melhorarem a capacidade de VM em situações de treino e competição bem como a dimensão cognitiva geral do QVMD, estão de acordo com os dados de outros estudos, onde estas áreas são igualmente passíveis de aperfeiçoamento e de maior utilização (ver Evans, Jones & Mullen, 2004). As diferenças a este nível prendem--se fundamentalmente com o facto de outras investigações terem constatado efeitos mais generalizados nos vários domínios avaliados pelo QVMD, relativos à função cognitiva e motivacional da VM (ver Cumming & Hall, 2002).…”
Section: Discussionunclassified
“…Os avanços têm tornado o jogo altamente competitivo onde os atletas se aperfeiçoem constantemente, tanto a nível físico, quanto psicológicos, ou especificamente mecanismos neurais sejam envolvidos na percepção e identificação das ações motoras individuais como de seus adversários, assim servindo de base para um melhor desempenho (Morales et al, 2009). Alguns estudos têm investigado tais aspectos em diferentes modalidades esportivas (Evans, Jones & Mullen, 2004;Munroe, Giacobbi, Hall & Weinberg, 2000;Cumming & Hall, 2002;Calmels, Berthoumieux & d'Arripe-Longueville, 2004 Como pôde ser percebido, ampliar a experimentação com realidades diferentes utilizando técnica de imaginação para o desportista não deixa de ser uma proposta interessante, enquanto prática que pode afetar o desempenho desses atletas. O processo de treinamento psicológico busca como um todo o equilíbrio emocional revertido em ações motoras acertadas.…”
Section: Introductionunclassified